Nevrogena motnja delovanja črevesa - Saksida, Ana (Rehabilitacija (Ljubljana), 2023)
The term neurogenic bowel dysfunction (NBD) refers to bowel dysfunction due to the damage to the nervous system that regulates bowel function. It affects a large portion of patients with neurological disorders, along with their family members and caregivers. Consequently, it is also often encountered during the rehabilitation of individuals with central neurological conditions (e.g., spinal cord injury, multiple sclerosis, Parkinson's disease, stroke), as well as in some disorders of the peripheral nervous system (e.g., cauda equina syndrome). The main symptoms of NBD include constipation, diarrhoea, faecal incontinence, bloating and abdominal pain. Due to the changes in bowel control, NBD has a significant negative impact on the quality of life, resulting in poor self-esteem, avoidance of social contacts and consequent social isolation. The clinical presentation of NBD depends on the location and extent of neurological impairment. Broadly speaking, NBD presents in two distinct clinical patterns: injuries above the conus medullaris result in the upper motor neurone syndrome (hyper-reflexic bowel), while injuries at the conus medullaris or cauda equina result in the lower motor neurone syndrome (flaccid bowel). Currently available literature strongly supports an individualised stepwise, multidisciplinary approach to the management of NDC, which should be tailored to the individual’s situation based on their symptoms and lifestyle preferences. Management of NBD includes modifications in diet, lifestyle, optimisation of medical therapy, and also surgeryThe term neurogenic bowel dysfunction (NBD) refers to bowel dysfunction due to the damage to the nervous system that regulates bowel function. It affects a large portion of patients with neurological disorders, along with their family members and caregivers. Consequently, it is also often encountered during the rehabilitation of individuals with central neurological conditions (e.g., spinal cord injury, multiple sclerosis, Parkinson's disease, stroke), as well as in some disorders of the peripheral nervous system (e.g., cauda equina syndrome). The main symptoms of NBD include constipation, diarrhoea, faecal incontinence, bloating and abdominal pain. Due to the changes in bowel control, NBD has a significant negative impact on the quality of life, resulting in poor self-esteem, avoidance of social contacts and consequent social isolation. The clinical presentation of NBD depends on the location and extent of neurological impairment. Broadly speaking, NBD presents in two distinct clinical patterns: injuries above the conus medullaris result in the upper motor neurone syndrome (hyper-reflexic bowel), while injuries at the conus medullaris or cauda equina result in the lower motor neurone syndrome (flaccid bowel). Currently available literature strongly supports an individualised stepwise, multidisciplinary approach to the management of NDC, which should be tailored to the individual’s situation based on their symptoms and lifestyle preferences. Management of NBD includes modifications in diet, lifestyle, optimisation of medical therapy, and also surgery.
Keywords: bowel regime; constipation; faecal incontinence; Fecal Incontinence; flaccid bowel; hiperrefleksno črevo; hyperreflexic bowel; nehotno uhajanje blata; ohlapno črevo; rehabilitation; režim odvajanja blata; zaprtje